2006
DOI: 10.2190/1g77-3371-k225-7840
|View full text |Cite
|
Sign up to set email alerts
|

The Creation of Virtual and Face-to-Face Learning Communities: An International Collaboration Experience

Abstract: This article examines the use of technology in higher education to support an international collaboration between 2 graduate seminars in cognition and instruction, one in Mexico and another in Canada. The culture of both seminars is described in the context of using computer mediated collaboration systems. The online collaboration between and within the 2 groups happened through the use of the communications tools available in WebCT, a Web-based course management system. The analyses reveal the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Technology can create communities of learners across international boundaries (Ertmer et al, 2011;Lai & Law, 2006;Lajoie et al, 2006;Peters & Slotta, 2010) but working in nonwestern cultures can pose challenges (e.g., Hmelo-Silver, 2012; see Hung & Loyens, 2012). We examine the manner in which online communities evolve by using the Community of Inquiry (COI) framework that describes learning from a social-constructivist approach (Garrison, Anderson & Archer, 2000).…”
mentioning
confidence: 99%
“…Technology can create communities of learners across international boundaries (Ertmer et al, 2011;Lai & Law, 2006;Lajoie et al, 2006;Peters & Slotta, 2010) but working in nonwestern cultures can pose challenges (e.g., Hmelo-Silver, 2012; see Hung & Loyens, 2012). We examine the manner in which online communities evolve by using the Community of Inquiry (COI) framework that describes learning from a social-constructivist approach (Garrison, Anderson & Archer, 2000).…”
mentioning
confidence: 99%
“…Teachers who are shown examples on how to provide constructive critiques and how to properly challenge each other may be more productive and comfortable participating in the online discussion as time progresses. For instance, existing research has indicated Modeling activities such as the consideration of others' ideas before posting messages can result in a more comfortable environment and in more interactive dialogues in the online settings (Lajoie, Garcia, Berdugo, Marquez, Espindola, & Nakamura, 2007). Likewise, modeling reciprocal and active participation may lead to quality online dialogues (Reinhart, Slowinski, & Anderson, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As well, cultural differences have the potential to impact projects in various ways. The communication and work styles of the participants as well as differences in interpretation of situations and directions, and significant language barriers can cause issues (Lajoie et al 2006).…”
Section: Principles Of Creativity and Group Collaborationmentioning
confidence: 99%